New Insights into Optimal Acoustic Feedback Cancellation - Nakagawa, C. Renato C.; Nordholm, Sven; Yan, Wei-Yong (IEEE Signal Processing Society, 2013)
In this letter, we present new insights into the bias problem for acoustic feedback cancellation when a probe signal approach is used. The optimum solution of the feedback canceler is not the feedback path but the product of the feedback path and the sensitivity function and hence, the solution is biased. The novelty of this paper also consists of the derivation of the conditions for unbiased feedback cancellation when a probe signal is used as input to the canceler. An adequate delay in the forward path is necessary to reduce, or remove the bias term. The theoretical analysis is verified with simulation results.